Understanding The Millennial Generation Behavior In Using Digital Banking - Baraba, Rania Abdul Aziz; Mahmudi, Mahmudi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This study aims to examine the effect of Perceived Usefulness, Perceived Ease of Use, Perceived Security, and Perceived Risk on the millennial generation’s attitude toward using Digital Banking. Furthermore, this study examines whether the attitude toward using digital banking influences the behavior in using digital banking Methodology/approach – This research is conducted through a quantitative approach. The sample of this study is the millennial generation which is proxied by undergraduate students. This research uses a convenience sampling method. The data collection was done by distributing online questionnaires via google form with a total sample of 111 respondents. The data analysis technique used is Structural Equation Modelling (SEM) with SmartPLS 3.0 software. Findings – It was found that Perceived Usefulness, Perceived Ease of Use, and Perceived Security has a positive significant effect on attitude toward the use of digital banking. Whereas Perceived Risk has a negative significant effect on attitude toward the use of digital banking. Last but not least attitude towards the use of digital banking has a positive significant effect on the use of digital banking. Novelty/value – The millennial generation is the generation that determines the current and future economies. Decisions in the use of financial technology among millennials are important to identify the attributes of financial technology that are their choice. This research provides insight into the factors that influence the attitudes and interests of the millennial generation in the use of financial technology that has not been widely studied.